THE MILLENIAL GENERATION, HADITH MEMES, AND IDENTITY POLITICS: The New Face of Political Contestation in Contemporary Indonesia - Imron, Ali (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Since society has been encountering the advanced technology of smartphones, the internet has become the most crowded channel as well as a noisy stage for disputes on religious issues. The preceding disagreement on hadith that manifested in thick books has now transformed into pictures or, I should call, hadith memes. Using the theory of Richard Dawkins, this article maps the forms of disputes involving hadith that are represented by memes. This qualitative research places those memes as the material object, while the messages provided by the hadith as the formal object. The reason behind the use of Dawkins’ theory is that those memes do not explicitly contain messages alone, but also sharp identity politics, criticism, contestation, satire, cynicism. As a result, this research maps hadith memes that are distributed on the internet into four categories. They are formed with straightforward messages and satires, containing ideological ideas of several religious groups in order to maintain their existence as well as win the contestation for power.